COMPARISON OF MATA-NI-PACHEDI ELEMENTS IN CONTEMPORARY WORK - Chandiwala, Mansi A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This ancient textile art form, known as Mata-ni-Pachedi, originates from Gujarat in India and brings with it profound cultural and spiritual importance. These fabrics, which were originally used as portable shrines, now function as visual storytelling, typically representing the goddess Durga or Kali via their imagery. Mata-ni-Pachedi is a traditional art form that draws inspiration from the storytelling traditions of the Waghari culture. It is traditionally constructed using hand-drawn images and natural dyes. This art form has developed into a contemporary practice over the course of the last several years, making use of both classic themes and current elements. Artists are increasingly extending beyond the realm of religious symbolism by incorporating social, environmental, and global issues into their work. In this case study, the change of Mata-ni-Pachedi is investigated by contrasting traditional features with modern interpretations. Particular attention is paid to topics such as motifs, symbolism, color palettes, linework, spatial arrangement, and thematic content.